Co-benefits of nonpharmaceutical intervention against COVID-19 on infectious diseases in China: A large population-based observational study - Jianpeng Xiao; Jiya Dai; Jianxiong Hu; Tao Liu; Dexin Gong; Xing Li; Min Kang; Yan Zhou; Yihan Li; Yi Quan; Guanhao He; Ruoxi Zhong; et al. (Elsevier, 2021)
Background: Nonpharmaceutical interventions (NPIs) are public health measures that aim to suppress the transmission of infectious diseases, including border restrictions, quarantine and isolation, community management, social distancing, face mask usage, and personal hygiene. This research aimed to assess the co-benefits of NPIs against COVID-19 on notifiable infectious diseases (NIDs) in Guangdong Province, China.Methods: Based on NID data from the Notifiable Infectious Diseases Surveillance System in Guangdong, we first compared the incidence of NIDs during the emergency response period (weeks 4-53 of 2020) with those in the same period of 2015-2019 and then compared that with the expected incidence during the synchronous period of 2020 for each city by using a Bayesian structural time series model.Findings: A total of 514,341 cases of 39 types of NIDs were reported in Guangdong during the emergency response period in 2020, which decreased by 50·7% compared with the synchronous period during 2015-2019. It was estimated that the number of 39 NIDs during the emergency response in 2020 was 65·6% (95% credible interval [CI]: 64·0% - 68·2%) lower than expected, which means that 982,356 (95% CI: 913,443 - 1,105,170) cases were averted. The largest reduction (82·1%) was found for children aged 0-14 years. For different categories of NIDs, natural focal diseases and insect-borne infectious diseases had the greatest reduction (89·4%), followed by respiratory infectious diseases (87·4%), intestinal infectious diseases (59·4%), and blood-borne and sexually transmitted infections (18·2%). Dengue, influenza, and hand-foot-and-mouth disease were reduced by 99·3%, 95·1%, and 76·2%, respectively. Larger reductions were found in the regions with developed economies and a higher number of COVID-19 cases.Interpretation: NPIs against COVID-19 may have a large co-benefit on the prevention of other infectious diseases in Guangdong, China, and the effects have heterogeneity in populations, diseases, time and space.Funding: Key-Area Research and Development Program of Guangdong Province